An Application of Data Mining in the Management of E-learning Platform - Pietruszkiewicz, Wiesław; Dżega, Dorota (Zastosowanie eksploracji danych w zarządzaniu platformą e-learningową, 2010)
In this paper we present an application of data mining in education, where the management of e-learning platform was supported by extraction of users activity features and clustering of users' profiles. It allowed us to identify groups of users with a similar activity and to observe their performance. While the majority of other researches focus on the analysis of students, we investigated teachers' behaviour. The experiments presented herein were performed on the real data coming from Moodle platform. We have proposed a smoothing model in the form of a dynamic system which was used to transform the logged events into time series of activities. These series were later used to cluster teachers' performance and to divide them into three groups: active, moderate and passive users. We claim that an increase of e-learning quality requires responsible persons not only to observe students but also to evaluate teachers. The gathered information may be used to identify potential teachers problems, e.g., technical difficulties or low e-learning platform skills.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 104, s. 60-70
Keywords: clustering; e-learning; kernel k-means; k-medoids